(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
Phlegmona, also referred to as phlegmon, is a complex and often challenging medical condition characterized by a spreading, inflammatory, and purulent process within the subcutaneous tissues and fascial planes. This thesis aims to provide a comprehensive understanding of phlegmona, including its pathophysiology, clinical manifestations, and contemporary management strategies. By synthesizing current research and clinical knowledge, this thesis seeks to contribute to the broader medical understanding of phlegmona and inform clinical practices to improve patient outcomes.